Repetitive DNAs and differentiation of the ZZ/ZW sex chromosome system in the combtail fish Belontia hasselti (Perciformes: Osphronemidae) - Oliveira, Alan Moura de; Deon, Geize Aparecida; Sember, Alexandr; Goes, Caio Augusto Gomes [UNESP]; Supiwong, Weerayuth; Tanomtong, Alongklod; Porto-Foresti, Fábio [UNESP]; Utsunomia, Ricardo [UNESP]; Liehr, Thomas; Cioffi, Marcelo de Bello (Springer Nature, 2025)
Background: Java combtail fish Belontia hasselti (Cuvier, 1831), a member of the Osphronemidae family, inhabits lakes and rivers throughout Southeast Asia and Sri Lanka. Previous cytogenetic research revealed it possesses a diploid chromosome number of 48 chromosomes with a female-heterogametic ZZ/ZW sex chromosome system, where the W chromosome is distinguishable as the only metacentric element in the complement. Female-heterogametic sex chromosome systems seem to be otherwise surprisingly rare in the highly diverse order Perciformes and, therefore, B. hasselti provides an important comparative model to evolutionary studies in this teleost lineage. To examine the level of sex chromosome differentiation in B. hasselti and the contribution of repetitive DNAs to this process we combined bioinformatic analyses with chromosomal mapping of selected repetitive DNA classes, and comparative genomic hybridization. Results: By providing the first satellitome study in Perciformes, we herein identified 13 satellite DNA monomers in B. hasselti, suggesting a very low diversity of satDNA in this fish species. Using fluorescence in situ hybridization, we revealed detectable clusters on chromosomes only for four satellite DNA monomers. Together with the two mapped microsatellite motifs, the repeats primarily accumulated on autosomes, with no distinct clusters located on the sex chromosomes. Comparative genomic hybridization showed no region with accumulated female-specific or enriched repeats on the W chromosome. Telomeric repeats terminated all chromosomes, and no additional interstitial sites were detected. Conclusion: These data collectively indicate a low degree of sex chromosome differentiation in B. hasselti despite their considerable heteromorphy. Possible mechanisms that may underlie this pattern are discussed.
Keywords: Fishes; Isochromosome; Molecular cytogenetics; Satellitome; Sex chromosome evolution; Teleostei